دور مستشار التوجيه والإرشاد المدرسي والمهني في الحد من ظاهرة الإخفاق المدرسي - لكحل أميمة; غانم حدة (University of Eloued جامعة الوادي, 2023)
ملخص الدراسة هدفت الدراسة إلى الكشف عن دور مستشار التوجيه والإرشاد المدرسي والمهني في الحد من ظاهرة الإخفاق المدرسي لدى تلاميذ المرحلة المتوسطة. وتمحورت إشكالية الدراسة حول التساؤل الرئيسي التالي: هل لمستشار التوجيه والإرشاد المدرسي والمهني دور في الحد من ظاهرة الإخفاق المدرسي لدى تلاميذ المرحلة المتوسطة ؟ وتضمنت الدراسة فرضيتينكالآتي: 1- لنشاط الحصص الاعلامية دور في الحد من ظاهرة الاخفاق المدرسي 2- لنشاط المقابلات الارشادية والمتابعة دور في الحد من ظاهرة الاخفاق المدرسي . وقد تم استخدام استبيان من إعداد الطالبتين،ولهذا الغرض اختيرت عينة مكونة من 40 مستشارا من متوسطات بلديتي المغير وجامعة. كما تم الاعتماد على المنهج الوصفي ، حيث مكننا من وصف ظاهرة الإخفاق المدرسي ، ووصف أدوار المستشار وتحليل معطياتها وصولا إلى النتائج . وبعد مناقشة التساؤل العام والتساؤلات الفرعية للدراسة وتحليل معطيات الدراسة، توصلنا إلى النتائجالتالية والتيمفادها : • أن لمستشار التوجيه والارشاد المدرسي والمهني دور في الحد من ظاهرة الإخفاق المدرسي. • ان للحصص الإعلامية التي يقوم بها المستشار دور في الحد من ظاهرة الإخفاق المدرسي. • أن للمقابلات الإرشادية التي يقوم بها المستشار دور في الحد من ظاهرة الإخفاق المدرسي.   Study Summary The study aimed to reveal the role of the school and vocational guidance andcounsellingcouncillor in reducing the phenomenon of School failure of middle school students. The problematic of the study revolved around the following main question: Does the school and vocational guidance counsellor have a role in reducing The phenomenon of school failure among middle school students ? The study included three sub –hypotheses as follows: • The councillor has a role in reducing the phenomenon of school failure • Media classes have a role in reducing the phenomenon of school agreement • The activity of counselling interviews and follow up has a role in reducing the phenomenon of school agreement • Counselling and follow up interviews have a role in reducing the phenomenon of school failure A questionnaire prepared by the two students was used، and for this purpose a sample of 40 councillors was selected from the averages of my municipality The descriptive approach was also relied upon، as it enabled us to describe the phenomenon of school failure، describe the role of the councillor and analyse its data to reach the results. After discussing the general question and sub question of the study and analysing the data of the study، we reached the following results to the effect. The councillor of school and vocational guidance and counselling has a role in reducing the phenomenon of school failure. The descriptive approach was also relied upon، as it enabled us to describe the phenomenon of school failure، and to describe the roles of the councillor and analyse its data to reach the results After discussing the general question and the sub question of the study and analysing the data of the study، we reached the following results، which are based on : The councillor of school and vocational guidance and counselling has a role in reducing the phenomenon of school agreement + The media sessions conducted by the councillorhave a role in reducing the phenomenon if school failure +The counselling interviews conducted by the councillor have a role in reducing the phenomenon of school failure
دراسة ميدانية على عينة من مستشاري التوجيه والإرشاد المدرسي والمهني ببلديتي المغير وجامعة
مذكرة ماستر علم الاجتماع تخصص علم اجتماع التربية
Keywords: مستشار التوجيه; Conseiller d'orientation; Guidance counselor; الإرشاد المدرسي; Orientation scolaire; School guidance